Women’s Language Features Used by Indonesian Female Bloggers - Annisa Aga Pebrianti (Universitas Pendidikan Indonesia (UPI), 2013)
The study entitled Women’s Language Features Used by Indonesian Female Bloggers aims to investigate women’s language features, the frequency of the features, and the possible reasons of using the features by female bloggers. The data were in the form of written text of Blogspot.com, published from October 2011 to September 2012, which consists of several bloggers’ activities such as their routines, business, fashion, and special events. The main theory of Robin Lakoff (1975) was used to analyze the data. Lakoff (1975) proposed ten women’s language features but this study only adopted nine features in the form of written text namely lexical hedges or fillers, tag question, empty adjectives, precise color terms, intensifiers, hypercorrect grammar, superpolite forms, avoidance of strong swear words, and emphatic stress. The findings reveal that there were ninety-seven postings which can be categorized into eight features. However, intensifiers tend to be the most frequent feature used by the female bloggers (34.92%), followed by empty ajectives (5.71%), and the least is avoidance of strong swear words (0.27%). Moreover, regarding the reasons by using the features is most respondents claimed that they use those features because they tend to reflect uncertainty and reflect women’s lack of confidence in conversation. In contrast, only few of respondents who stated that they use those features because women have higher level of vocabularies than men.Keyword: Women’s language features; Blog